Alport syndrome – a rare kidney disease of domestic dog Canis lupus familiaris - Kania, Agata; Gruszczyńska, Joanna; Bartyzel, Bartłomiej J.; Grzegrzółka, Beata; Mikuła, Małgorzata (Folia Pomeranae Universitatis Technologiae Stetinensis Agricultura, Alimentaria, Piscaria et Zootechnica, 2016)
Alport syndrome is a rare, hereditary renal disease which is the result of a lack of one chain of type IV collagen (α3, α4, and α5). Type IV collagen is a basic structural component of the glomerular basement membrane. Alport syndrome has been reported in humans, mice and domestic dogs. Mutations in COL4A3 and COL4A4 genes are both of recessive and dominant type; however, the most common mutations in COLL4A5 gene are linked to X sex chromosome. These mutations render the synthesis of (α3, α4, α5) chain impossible, thus the resulting type IV collagen does not have its proper structure and filtration of plasma is impaired, leading to progressive renal insufficiency and failure. With the current state of medical knowledge the only therapy, delaying the pathological processes, is limited to dialysis and kidney transplantation. This paper presents information on symptoms of Alport syndrome, as well as genetic basis and molecular effects of mutations causing the disease. It also offers dog breeders some advice, based on the available literature, in order to facilitate making the right breeding decisions. Zespół Alporta jest rzadką dziedziczną chorobą nerek spowodowaną brakiem jednego z łańcuchów kolagenu typu IV (α3, α4, α5). Kolagen typu IV jest podstawowym elementem budującym błonę podstawną kłębuszka nerkowego. Zespół Alporta występuje zarówno u człowieka, myszy, jak i psa domowego. Mutacje w obrębie genów COL4A3 i COL4A4 mają charakter zarówno recesywny, jak i dominujący. Jednakże najliczniejsza grupa mutacji występująca w obrębie genu COL4A5 jest sprzężona z chromosomem płci X. Poprzez mutacje w tych genach synteza łańcuchów: α3, α4, α5 jest niemożliwa, w następstwie czego kolagen typu IV nie jest poprawnie zbudowany, nie może w pełni następować filtracja osocza. Konsekwencją zaburzeń w filtracji jest postępująca niewydolność nerek i w efekcie zaprzestanie pracy nerek. Przy obecnej wiedzy medycznej jedynym sposobem na opóźnienie postępu choroby – zespołu Alporta są dializy i przeszczep nerki. W niniejszym ...